Potensi Hutan Mangrove Sebagai Daya Tarik Wisata - Syamsu Rijal; Faizal Akbar Zainal; Muh. Zainuddin Badollahi (Pusaka: Journal of Tourism, Hospitality, Travel and Business Event, 2020)
The Research of the potential of mangrove forests as an educational tourism is a survey research that focuses on the richness of mangrove forest ecosystems and its potential as an economic driver for the community through educational tourism activities. This research was conducted in the Idaman mangrove forest, Tarowang sub-district, Jeneponto South Sulawesi province. Data collection techniques used were through questionnaires, interviews, and documentation. The results showed that the characteristics of the Idaman mangrove forest consist of various species of mangrove plants, birds, and other mangrove ecosystems that are very potential as a tourist attraction. The potential of the mangrove forest has not been optimized by the communities around tourism area so that it has not yet optimally contributed as an economic source. The constraints in developing of the Idaman mangrove forest as a tourist attraction are the absence of a community-based tourism development and management model on the attractiveness of the Idaman mangrove forest, the low creativity and capacity of the community, as well as limited tourism support facilities. The recommended model for developing mangrove forests is educational tourism based through nursery activities and planting of mangrove forests for conservation, utilization and diversification of mangrove forest products as culinary and handicraft products.